THE RELATIONSHIP BETWEEN GENDER AND UNDERGRADUATE PHYSICS STUDENTS’ LABORATORY PERFORMANCE - Ananingtyas, Ratika Sekar Ajeng; Suwasono, Purbo; Kurniawan, Bakhrul Rizky; Prawitasari, Prawitasari; Munfaridah, Nuril (Universitas Tanjungpura, 2026)
Laboratory activities play a central role in fundamental physics courses because they support the development of procedural skills, experimental reasoning, and practical problem solving. This study investigates whether gender and class group are associated with the laboratory performance of undergraduate physics students. The participants were 54 first-year physics students enrolled in a fundamental physics laboratory course. Laboratory performance was measured through structured observation rubrics focusing on procedural accuracy and practical engagement, as well as an individual performance test assessing experimental readiness and data interpretation skills. Descriptive analysis showed that the mean score for performance observation was 88.44, while the mean score for performance test was 67.04. Both variables were non-normally distributed (Shapiro-Wilk = 0.92, p < 0.001) but showed homogeneous variances across gender and class group. Spearman analysis revealed a moderate positive association between observation and test scores ( = 0.399, p = 0.0028), suggesting that students who performed well during laboratory activities tended to achieve higher scores on individual performance test. Wilcoxon test showed that gender was linked to differences in observation scores (W = 480, p = 0.03748) but not on test scores (W = 368.5, p = 0.8892), whereas class group showed the opposite pattern. Overall, the findings highlights the importance of using multiple assessment approaches to capture laboratory performance more comprehensively and to avoid overinterpreting gender differences as deficits. The results contribute context-specific evidence form Indonesian physics education and support efforts to promote more equitable laboratory learning environments.